PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM PEMBINAAN AKHLAK SISWA DI MAN 2 LAMONGAN - Sholeh, Mochammad; Tamaji, Sampiril Taurus; Ayu, Intan (Fakultas Agama Islam, 2024)
This research aims to find out the role of Islamic Religious Education (PAI) teachers in developing morals in class. This research is qualitative research. The subjects of this research were teachers and students of class XII at MAN 2 Lamongan. The data collection method uses observation, interview and documentation techniques. Techniques to ensure the validity of the data are analyzed, then the data is analyzed using triangulation and conclusions are drawn.The results of the research can be concluded that: 1) The role of Islamic Religious Education (PAI) teachers in developing morals in students can be categorized as good in its implementation, Islamic Religious Education (PAI) teachers have implemented exemplary methods, advice and supervision for students. 2) Efforts made by Islamic Religious Education (PAI) teachers in developing students' morals, namely: a) Providing guidance to students; b) Always exemplify good behavior such as always saying hello, being polite, courteous, disciplined and c) Providing enthusiasm for learning and teaching an attitude of self-sacrifice. 3) Supporting factors in developing morals in students are: a) Facilities; b) Educators and c) Students are easy to advise. 4) Inhibiting factors in developing students' morals are: a) Students are difficult to advise. b) Poor environment and c) Lack of support from parents.